PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN PADA PENJUALAN SPREI USAHA RAKYAT DI KOTA MEDAN - Anshar, M.; Harahap, Ahmad Taufiq (Journal Economic Management and Business, 2025)
Customer loyalty is a customer's commitment to a brand, store, or supplier that is seen in repeat purchasing behavior. Several factors can shape customer loyalty, including price and service quality. The purpose of this study is to determine the effect of price and service quality, both partially and simultaneously, on customer loyalty at the Usaha Rakyat Bed Sheet Store in Medan City. This study was conducted using a quantitative method with a descriptive research type. The population in this study were all customers who had made regular purchases at the Usaha Rakyat Bed Sheet Store in Medan City with a minimum purchase requirement of 2 times. The sample used was 30 respondents and the technique used was non-probability sampling. Data analysis used multiple linear regression analysis, significance testing, and determination testing. The results of this study indicate that the price variable does not have a significant effect on customer loyalty, while the service quality variable has a significant effect on customer loyalty. Simultaneously, it shows that price and service quality have a significant effect on customer loyalty at the Usaha Rakyat Bed Sheet Store in Medan City. The results of the determination test show that 57% of customer loyalty is influenced by price and service quality, while the remaining 43% is influenced by other variables not explained in this study.